Militarisation of citizenship education curriculum in Turkey. Issue 1 (2nd January 2019) - Sen, Abdulkerim
ABSTRACT: In response to the United Nation's (UN) Decade for Human Rights Education initiative, the Turkish Ministry of National Education changed the title of citizenship education courses from 'Citizenship Studies' to 'Citizenship and Human Rights Education' in 1995. However, this curriculum reform was overshadowed by the rise to power of a political Islamist party. The secularist military toppled the first Islamist party-led government in the name of preserving the principle of laicism. Announced after the 1997 coup, the main textbook for the citizenship and human rights education course showed a profound influence of the militaristic discourses as evidenced by the negative depiction of the Kurdish people and political Islamists and the hagiographic portrayal of Atatürk and the army. By drawing on interviews with key informants, archival/public policy documentation and textbooks, this paper argues that the curriculum reform began with the participation in the UN initiative ended with the military's instrumentalisation of the subject because it was launched with no recognition of Turkey's human rights and democracy problems.